Peran Penyuluh Agama Islam dalam Pemberdayaan Mental dan Spiritual Warga Binaan Pemasyarakatan Rutan Kelas IIB Sukadana - Devi Tias Pratiwi; M. Nasor; Rini Setyawati; M. Mawardi J (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the role of Islamic Religious Counselors in the mental and spiritual empowerment of inmates at the Sukadana Class IIB Detention Center. The study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation of religious counselors, prison officers, and inmates. The results indicate that religious counselors play a strategic role as educators, motivators, counselors, and facilitators in religious development. The development program is implemented through religious study, prayer guidance, Quranic study, religious consultations, and activities commemorating Islamic holidays. These activities contribute to increasing religious awareness, inner peace, self-control, and optimism among inmates to improve their lives after release. Supporting factors include cooperation between the Ministry of Religious Affairs and the detention center, while inhibiting factors include limited facilities and low motivation among some inmates. This study concludes that Islamic religious counselors play a crucial role in shaping the mental and spiritual well-being of inmates, thus supporting the success of the social rehabilitation process.